Theta-burst modulation of mid-ventrolateral prefrontal cortex affects salience coding in the human ventral tegmental area. (1st April 2018) - Ulrich, Martin; Lorenz, Sabrina; Spitzer, Markus W.; Steigleder, Leon; Kammer, Thomas; Grön, Georg
Abstract: In the context of hedonic (over-)eating the ventral tegmental area (VTA) as a core part of the dopaminergic reward system plays a central role in coding incentive salience of high-caloric food. In the present study, we used functional magnetic resonance imaging (fMRI) to investigate whether transcranial magnetic theta-burst stimulation (TBS) over the right mid-ventrolateral prefrontal cortex (mid-VLPFC) can induce modulation of calorie-sensitive brain activation in the VTA. The prefrontal location for TBS had been predetermined by seed-based resting-state fMRI with a functionally defined portion of the VTA serving as seed region obtained from an independent second fMRI experiment. In a sample of 15 healthy male participants, modulation of calorie-sensitive VTA activation did not significantly differ between the two TBS protocols. Comparisons with baseline revealed that both TBS protocols significantly affected calorie-sensitive neural processing of the mid-VLPFC in a rather similar way. In the VTA significant modulation of calorie-sensitive activation was observed after continuous TBS, whereas the modulatory effect of intermittent TBS was less reliable but also associated with a decrease of activation for high-caloric food images. Neurostimulation of right mid-VLPFC is suggestive as a main entry point of downstream signal changes for high- and low-caloric food cues that could enforce a shift in valuating stimuli of initially different incentive salience.